Nano- and microfabrication for overcoming drug delivery challenges - Kam, Kimberly R. (2013)
This highlight article describes current nano- and microfabrication techniques for creating drug delivery devices. We first review the main physiological barriers to delivering therapeutic agents. Then, we describe how novel fabrication methods can be utilized to combine many features into a single physiologically relevant device to overcome drug delivery challenges.